2017
DOI: 10.1016/j.jbiotec.2016.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant capacities of fucoxanthin-producing algae as influenced by their carotenoid and phenolic contents

Abstract: Natural antioxidants from sustainable sources are favoured to accommodate worldwide antioxidant demand. In addition to bioprospecting for natural and sustainable antioxidant sources, this study aimed to investigate the relationship between the bioactives (i.e. carotenoid and phenolic acids) and the antioxidant capacities in fucoxanthin-producing algae. Total carotenoid, phenolic acid, fucoxanthin contents and fatty acid profile of six species of algae (five microalgae and one macroalga) were quantified followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
68
2
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(98 citation statements)
references
References 40 publications
12
68
2
9
Order By: Relevance
“…Foo et al . () reported that the ABTS of the microalgae Isochrysis galbana (21.55 mg TE g −1 alga) and Chaetoceros calcitrans (16.92 mg TE g −1 alga) was lower compared to the findings in our study.…”
Section: Resultscontrasting
confidence: 89%
See 2 more Smart Citations
“…Foo et al . () reported that the ABTS of the microalgae Isochrysis galbana (21.55 mg TE g −1 alga) and Chaetoceros calcitrans (16.92 mg TE g −1 alga) was lower compared to the findings in our study.…”
Section: Resultscontrasting
confidence: 89%
“…In comparison with macroalgae, Foo et al . () showed that microalgae ( Chaetoceros calcitrans with 5.13 mg Fx g −1 alga) had higher fucoxanthin compared to macroalgae, and it could be up to 18.23 mg Fx g −1 alga in microalgae Isochrysis aff. galbana (Kim et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results were then expressed as milligram fucoxanthin per gram dry weight biomass (mg FX.g −1 .DW) as reported in Foo et al [1].…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…High performance liquid chromatography (HPLC) eluted fucoxanthin at the 7.008±0.024th min. This data article refers to the research article ‘‘Antioxidant capacities of fucoxanthin-producing algae as influenced by their carotenoid and phenolic contents’’ Foo et al [1]; where a more comprehensive data interpretation and analysis is explained.…”
mentioning
confidence: 99%